An Anonymous Health Care System - Chase, Melissa; Lauter, Kristin (19th USENIX Security Symposium Workshop: HealthSec 2010, 2010)
When patients participate in today’s healthcare system, insurance companies and pharmacies have access to the sensitive patient care information, including medical conditions, diagnosis and treatment. We have designed an anonymous system in which patients can receive care from their physicians and the care providers can receive payment for their services, without the insurance companies and pharmacies learning which patients are being treated for which conditions.
19th USENIX Security Symposium Workshop: HealthSec 2010